The global land grab : beyond the hype - Kaag, Maria Margaretha Antonia; Zoomers, E. B. (Fernwood Publishing ; Zed Books, 2014)
The last two years have seen a huge amount of interest in the increasingly contentious issue of land grabbing - the large-scale acquisition of land in the global South. This in-depth and empirically diverse volume takes a step back from the hype to explore a number of key questions: does the 'global land grab' actually exist? If so, what is new about it? And what, beyond the immediately visible dynamics and practices, are the real problems? A comprehensive and much-needed intervention.